Periodontal Treatment Needs of Women Across Different Trimesters of Pregnancy - Mahnoor Tariq, Afeefa Shahbaz, Minahil Abbas, Asma Shakoor, Hira Butt, Fatima Irfan (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To find the difference in the periodontal treatment needs of females across different trimesters of pregnancy. Methodology: A cross sectional comparative study was conducted among 44 pregnant visiting the gynecology department of Sharif Medical and Dental College and Raiwind Polyclinic, Lahore (community outreach program of the institute). Data was collected using the Community Periodontal Index of Treatment Needs (CPITN) Results: The highest percentage of females (24%) requiring no treatment (TN0) were in their third trimester. The majority of females in their second trimester (85.7%) required oral hygiene instructions and had periodontal treatment needs (TN1) and those in their first trimester (83.3%) required Scaling and prophylaxis and Oral hygiene instructions (TN 2). Conclusion: The highest percentage of females with healthy periodontium were in their third trimester. Periodontal pocket depth of 4-5 mm were seen the most on the clinical examination of women in their second trimester but least in third trimester. The highest percentage of females requiring no treatment (TN0) were in their third trimester. The majority of females in their second trimester required oral hygiene instructions and had periodontal treatment needs (TN1) and those in their first trimester required Scaling and prophylaxis and Oral hygiene instructions (TN 2). Keywords: Periodontal treatment needs, first trimester, second trimester, third trimester, Community periodontal index for treatment needs (CPITN)